Analysis of Mobile Financial Services Utilization among Small Scale Businesses in Kiambu County, Kenya - ONONO, PEREZ; Karanja, Kenneth Kamau (Archives of Business Research, 2020)
This study examined the level of utilization of Mobile financial services among small scale businesses in Kiambu County. Primary data was obtained through interview administered questionnaire from 123 small scale businesses in Kiambu County. Using descriptive analysis the study found out that 48.8 percent of the businesses utilized mobile financial services. The mobile financial services utilized by the businesses included mobile money in phone, Pay bill Buy goods and services and mobile money bank accounts. Majority of the businesses used mobile money in phone. Businesses cited lack of mobile financial services devices by businesses, lack of mobile financial services incentives such as loyalty points, mobile money transaction charges, poor interoperability between networks, low acquaintance to mobile financial services transactions, service system breakdown, difficulties while accessing customer care services as major challenges in use of mobile financial services. The study concludes that mobile financial services are compliments other financial services in extending financial services to the unbanked sector in the county and recommends that systems development and improvement of service delivery by mobile network operators towards small scale businesses and enhanced legislations on data protection and cyber-crimes to protect users of mobile financial services towards increased use of the services.